2019
DOI: 10.1186/s11658-019-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 regulates milk biosynthesis and the proliferation of bovinemammaryepithelial cells through the mTOR signaling pathway

Abstract: BackgroundGlucose-regulated protein 78 (GRP78) is a member of the HSP70 protein family and a key endoplasmic reticulum chaperone. It has been revealed to play important roles both in the maturation, folding and transport of proteins and in cellproliferation. However, its involvement in milk biosynthesis or the proliferation of bovine primary mammary epithelial cells (BMECs) has yet to be established.MethodsThe expressions of GRP78 in BMECs stimulated with methionine, leucine, estrogen and prolactin were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In the present study, it was hypothesized that exogenous H 2 S could protect cartilage against TBHP-induced oxidative stress. The present study relied on the novel finding that GYY4137 displays physicochemical properties that may be related to the inhibition of ER stress-induced apoptosis ( 14 , 17 , 29 ) via the downregulation of the expression levels of CHOP, GRP78 and ATF6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, it was hypothesized that exogenous H 2 S could protect cartilage against TBHP-induced oxidative stress. The present study relied on the novel finding that GYY4137 displays physicochemical properties that may be related to the inhibition of ER stress-induced apoptosis ( 14 , 17 , 29 ) via the downregulation of the expression levels of CHOP, GRP78 and ATF6.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress induces cH apoptosis, which is associated with the pathogenesis of OA (27). GRP78 has been reported to serve as a critical mediator of ER stress, as demonstrated by decreased mTOR induction (28)(29)(30)(31)(32)(33). GRP78 was selected as a novel biomarker, as its level associated with cell process, cell integrity failure, and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is one of the important protein kinases. It can regulate a variety of physiological and pathological metabolisms in different tissues and organs through two downstream effectors, 4EBP1 and S6K. , In addition, studies have also shown that mTOR can promote lipid de novo synthesis through SREBP1, which controls the expression of genes involved in fat biosynthesis and decomposition. , Currently, mTOR is also used as the axial pathway for milk synthesis in BMECs . It has been proven that amino acids, fatty acids, and hormones can affect milk synthesis by regulating mTOR. , Therefore, the intensity of mTOR signal transduction directly determines the ability of milk synthesis in BMECs.…”
Section: Discussionmentioning
confidence: 99%
“…The ER stress is mainly caused by the accumulation of unfolded or misfolded protein inside the ER, and excess ER stress response also leads to cell damages [ 12 ]. GRP78 is a vital endoplasmic reticulum chaperone which can function in various processes except for ER stress including cell proliferation, protein maturation, folding and transport [ 17 ]. CHOP is a key molecule in the downstream of PERK, and ER stress can be mediated by the PERK-CHOP pathway [ 11 ].…”
Section: Discussionmentioning
confidence: 99%